Tigers - Murray, Julie, 1969- (2020)
"This book introduces readers to the unique features of tigers. Basic information is covered, such as habitat, life cycle, range, diet and threats."--
The biggest cat -- What they look like -- Where they live -- Hunting and eating -- Territories -- Swimming cats -- Tiger cubs.
Includes index.
Interest grade level: 2-5.
Reading grade level: 3.
Keywords: Tiger -- Juvenile literature; Tiger